Grid-Connected Solar Electric Systems. - Stapleton, Geoff (Earthscan expert series., 2012)
Solar electricity - or photovoltaics (PV) - is the world's fastest growing energy technology. It can be used on a wide variety of scales, from single dwellings to utility-scale solar farms providing power for whole communities. It can be integrated into existing electricity grids with relative simplicity, meaning that in times of low solar energy users can continue to draw power from the grid, while power can be fed or sold back into the grid at a profit when their electricity generation exceeds the amount they are using. The falling price of the equipment combined with various incentive schem.